Pengaruh Digital Advertising, Influencer Marketing Dan Product Quality Terhadap Minat Beli Konsumen Di E-Commerce Shopee (Studi Mahasiswa Pengguna Shopee di Negara Thailand dan Indonesia) - Putri, Berliana Imandari; Diana, Nur; Efendi, Erfan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research uses purchase intention as the dependent variable to see how the independent variables of digital advertising, influencer marketing and product quality can affect the purchase intention variable in students. The study used a survey method of non-probability sampling and purposive sampling with a sampling technique of judgment sampling, a predetermined sample of 90 with data analysis tests using SPSS ver 25. The results show that the independent variables of digital advertising, influencer marketing and product quality all have a positive and significant effect on the dependent variable of purchase intention. This shows that all independent variables contribute to understanding consumer behavior in the digital era, especially among college students as a potential market segment in the Southeast Asia region. For policy makers and e-commerce industry players, these results can be used as a foundation in designing marketing strategies that are more effective and in accordance with market characteristics in each country. Keywords: Digital Advertising, Influencer Marketing, Product Quality, Purchase Intention